Host factor RBMX2 promotes epithelial cell apoptosis by downregulating APAF-1’s Retention Intron after Mycobacterium bovis infection - Wang, Chao; Jiang, Yanzhu; Yang, Zhiming; Xu, Haojun; Khalid, Abdul Karim; Iftakhar, Tahira; Peng, Yongchong; Lu, Lu; Zhang, Lei; Bermudez, Luiz; Guo, Aizhen; Chen, Yingyu (Frontiers in Immunology, 2024)
Mycobacterium tuberculosis variant bovis (M. bovis) is a highly pathogenic environmental microorganism that causes Bovine tuberculosis (bTB), a significant zoonotic disease. "Test and culling" is the primary control measure currently, for it, but now it has proved to be inadequate in animals due to high susceptibility of this pathogen. Selective breeding for enhanced host resistance to bTB would be feasible to reduce the prevalence. In this study, we found a vital host-dependent factor, RBMX2, which could potentially promote M. bovis infection. By knocking it out, we investigated the function of RBMX2 during M. bovis infection, and we concluded that after M. bovis infection, embryo bovine lung (EBL) cells were significantly enriched in RNA splicing associated with apoptosis compared to WT EBL cells. Through protein/molecular docking, molecular dynamics simulations, and real-time quantitative polymerase chain reaction (RT-qPCR), we demonstrated that RBMX2 promotes apoptosis of epithelial cells by upregulating and binding to apoptotic peptidase activating factor 1 (APAF-1), resulting in alternative splicing of APAF-1 as a Retention Intron (RI). In our understanding, this is the first report of M. bovis affecting host epithelial cell apoptosis by hijacking the RBMX2 to promote intron splicing of its downstream APAF-1. These findings may be a significant contribution to developing novel TB prevention and control strategies.